El marketing de influencers su papel en la promoción de productos y servicios en Babahoyo - Carpio Moncada, Brithani Berenice (2025)
This research thesis demonstrates the impact of influencer marketing in the promotion of products and services in the city of Babahoyo, with the aim of evaluating the effectiveness of this strategy and determining the factors that influence consumer conviction, through a quantitative-quantitative approach methodology and the use of surveys applied to local merchants and consumers in general, it was identified that micro and nano influencers are generally those who give greater credibility to their product promotions due to authenticity, creativity and closeness to their followers. The results showed that influencer marketing has a positive impact on customer reach, interaction and conversion, although it depends greatly on the transparency and quality of the promoted content. It is observed that consumer trust is an important factor in the success of this strategy, since many respondents perceive that the information provided can be exaggerated in some way or often misleading. Based on this research, local brands and entrepreneurs are advised to work with smaller-scale influencers and encourage strategies based on authenticity and credibility. It is also suggested that training be implemented for merchants and influencers to ensure more ethical and effective marketing content in the digital environment.